Impact of Diabetes on Pregnancy-Related Cataract Formation: A Cross-Sectional Study - Abid, Abdul Rahman; Kamran, Areesha; Zulfiqar, Irsa; Memon, Farzana Rahim; Ali Khan, Sufian; Niazi, Zehra (Journal of Neonatal Surgery, 2025)
Background: Diabetes mellitus is highly prevalent among Pakistani women of reproductive age. Pregnancy-related metabolic changes may accelerate osmotic stress on the lens, leading to early cataract formation. Limited data exist on the burden of lens opacities specifically in diabetic pregnancies. Objective: To determine the frequency, severity, and predictors of cataract formation among pregnant diabetic women in Pakistan and correlate these findings with physiological glucose parameters. Methods: A cross-sectional study included 100 pregnant diabetic women (both GDM and pre-existing diabetes) from a tertiary care hospital in Rawalpindi. Each participant underwent Fasting blood glucose (FBG), HbA1c testing, Obstetric evaluation, Slit-lamp ophthalmic examination. Cataracts were graded using the LOCS III system. Data were analyzed using chi-square and Pearson correlation. Results: The prevalence of cataracts among the 100 participants was 32%.Nuclear cataract was seen in 18% cases, followed by cortical cataract in 9% and then posterior subcapsular cataract (PSC) in 5%. Women with poor glycemic control (HbA1c > 7%) had a significantly higher cataract rate (46%) compared to controlled diabetics (18%) (p = 0.004). A positive correlation was found between HbA1c and cataract score (r = 0.62). Conclusion: Cataract formation is common in diabetic pregnancies in Pakistan, especially in women with poor glycemic control. Early ophthalmologic screening should be integrated into antenatal care for diabetic pregnancies